2019
DOI: 10.3892/ol.2019.11181
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of peritumoral fibrosis after resection of pancreatic head cancer

Abstract: Prognostic value of peritumoral fibrosis (PF) in pancreatic head cancer after resection was evaluated. A total of 143 pancreatic cancer patients who underwent tumor resection were enrolled. All patients underwent routine preoperative examination, including contrast-enhanced computed tomography (CT) or magnetic resonance imaging (MRI). Patients receiving preoperative chemoradiation were excluded because it affects the proportion of fibrosis and cancer cells. Histopathological confirmation and classification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It thereby remains to be investigated in further research, whether the potential prognostic relevance derives from the reduced tolerability of chemotherapy due to general liver fibrosis or a potential negative prognostic impact of peritumoral fibrosis. Notably, for other tumor entities such as pancreatic head cancer, peritumoral fibrosis was shown to be associated with worse survival [ 27 ]. In CCA patients, cancer-associated fibroblasts (CAF), as well as extracellular matrix proteins, were shown to be associated with tumor growth and reduced survival [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It thereby remains to be investigated in further research, whether the potential prognostic relevance derives from the reduced tolerability of chemotherapy due to general liver fibrosis or a potential negative prognostic impact of peritumoral fibrosis. Notably, for other tumor entities such as pancreatic head cancer, peritumoral fibrosis was shown to be associated with worse survival [ 27 ]. In CCA patients, cancer-associated fibroblasts (CAF), as well as extracellular matrix proteins, were shown to be associated with tumor growth and reduced survival [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that BAG3 protein can be secreted by some cell types, in particular, pancreatic adenocarcinoma cells and cardiomyocytes, under oxidative stress 5,6 . Moreover, it has been shown that BAG3 secreted by pancreatic tumor cells induces the activation of Tumor‐Associated Macrophages (TAMs) through the binding to its receptor Interferon‐induced transmembrane protein (IFITM)‐2, which in turn activates p38 and PI3K and stimulates the production of molecules, such as interleukin (IL)‐6, that support the neoplastic growth.…”
Section: Introductionmentioning
confidence: 99%
“…4 It has been demonstrated that BAG3 protein can be secreted by some cell types, in particular, pancreatic adenocarcinoma cells and cardiomyocytes, under oxidative stress. 5,6 Moreover, it has been shown that BAG3 secreted by pancreatic tumor cells induces the activation of Tumor-Associated Macrophages (TAMs) through the binding to its receptor Interferon-induced transmembrane protein (IFITM)-2, which in turn activates p38 and PI3K and stimulates the production of molecules, such as interleukin (IL)-6, that support the neoplastic growth. A monoclonal antibody able to bind extracellular BAG3 can block its activity and to impair the tumor growth and the metastatic process in three different PDAC mouse models, thus confirming the relevance of the protein in the neoplastic cells-TAMs cross talk.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies, the number of variables on patients’ baseline characteristics investigated in this study should be supplemented. For example, estimated blood loss, lymph node harvest, preoperative albumin level, peritumoral fibrosis, and perioperative blood transfusion were also potential risk factors that would probably associate with both postoperative complications and long-term prognosis after resection of pancreas, which have been demonstrated in many previous studies 2–4 . Therefore, some vital variables be supplemented.…”
mentioning
confidence: 99%